Management Control in Contemporary Organization: Opportunities, Challenges and Research Directions - Arati Devi (International Journal of Engineering and Management Research, 2019)
This paper deals with management control as an important instrument for managing performances in modern organizations. The paper indicates to the circumstances in which classical theory of management control was created, and describes its process of functioning, with the specifics in large organizations. The aim is to point to some open questions and directions of further development of the management control, as well as to at least partially fill the gap that exists in the domestic literature. The conclusion is that the existing management control framework remains still valid. Open questions can be best resolved within the concept that observes this matter as a "package" of different control systems, not just those that are oriented to accounting-based performance measures.